Plan Parcial De Renovación Urbana Bosa Rio Tunjuelo (2022)
Different studies are presented related to the implications of the demographic growth of the city and its relation to the well-being and quality of life of the inhabitants. Dureau & Gouëset (2011), in an investigation “Forms of settlement and inequalities in displacement. The evolution of daily mobility in two popular peripheries of Bogotá: Soacha and Madrid (1993-2009)", show that the accelerated demographic growth in the city of Bogotá is parallel to the peripheral expansion given by the supply of transport and the increase in popular housing, this increases the possibilities of meeting the basic needs of the population that reaches the peripheral territory of the city.